Los determinantes económicos de la delincuencia en América Latina periodo 2000-2020. - Balarezo Badillo, Marcelo Alexander (2023)
Crime has become a constant problem that day by day disturbs thousands of people around the world, the high rates that occur over the years have generated a certain degree of concern, thus becoming a subject of study for several researchers, which have demonstrated the different approaches that seek to understand where the different economic, social, psychological and even cultural determinants of crime originate. The present work carries out one of the possible economic determinants that give rise to the increase in the crime rate with consequence in studies of homicides for the 16 countries of Latin America within the period 2000-2020. The structure of the investigation is given by the following chapters. The first chapter discloses the introduction, the problem statement and the postulation of the objectives, in order to introduce the reader to the subject. The second chapter covers the state of the art where the different studies related to the problem to be studied are detailed, as well as the different modeling applied, the same ones that include the transmission between the variables according to the study sector. For the third chapter, we proceed with an econometric modeling of generalized least squares with the use of panel data, which together with economic theory were able to demonstrate, through a collinearity effect, that the education and Gini variables were insignificant in the model. Finally, for the fourth chapter, the different conclusions were developed, as well as recommendations for which recognition was given to the negative effects that can occur if the determinants such as unemployment, education, urbanity are not treated correctly and on time through public policies that help development. and growth of society.